The Burden of Malnutrition among Adults Residing in Arba Minch Health and Demographic Surveillance Site (HDSS): A WHO STEPS Survey - Befikadu Tariku Gutema; Adefris Chuka; Mekdes Kondale; Gistane Ayele; Mesfin Kote; Zerihun Zerdo; Behailu Merdekios; Tsegaye Tsala; Alazar Baharu; Gebresilasea Gendisha Ukke (Journal of Nutrition and Metabolism)
Background. Malnutrition is one of the main underlying risk factors for the deaths due to different diseases. The aim of this study was to assess the prevalence and factors associated with underweight and overweight among adults residing in Arba Minch Health and Demographic Surveillance Site (HDSS), Southern Ethiopia. Methods. A community-based cross-sectional survey was conducted from April to June 2017. The data collection procedures and 3,368 calculated sample size were based on the World Health Organization (WHO) STEPwise approach to Surveillance guideline. Using the surveillance data of Arba Minch HDSS, simple random sampling technique was implemented to identify individuals for the study. To assess the presence of association, the multinomial logistic regression model was used. Results. The mean (SD) body mass index of the participants was 21.5 4.90 kg/m2. From 3,346 participants, 23.3% of the study participants were affected by malnutrition (10.8% and 12.5% were overweight and underweight, respectively). The prevalence of underweight was increased significantly among individuals aged 45–54 years and 55–64 years (adjusted odds ratio (AOR) 1.70 and 1.93, respectively) compared with those who were 25–34 years old. Belonging to households with higher wealth index quintile (2nd quintile AOR is 0.58 and 4th quintile AOR is 0.66) has decreased the chance of adult individual to be underweight compared with the poorest households. On the other hand, the prevalence of overweight was significantly higher among females (AOR 1.60), urban residents (AOR 1.72), those with formal education (primary AOR 1.89 and secondary and above AOR 1.94), and higher wealth index (5th quintile AOR 1.87). Conclusion. One in five adult individuals was malnourished in the study area. The double burden of malnutrition at the population level is becoming a challenge for this community, as both underweight and overweight are becoming prevalent. Sex, age, residency, educational status, current tobacco use, occupation, and wealth index were identified as important determinates of under- and overweight.